Analysis of Mobility Issues and Politicization of the Civil Service in Public Administration in Romania - Tudorel ANDREI; Marius PROFIROIU; Bogdan OANCEA (Transylvanian Review of Administrative Sciences, 2012)
This paper presents some issues related to civil servants mobility and politicization of the civil service in Romania during 2000-2010, using qualitative and quantitative methods for analyzing data collected from a sample of employees working in public administration. The analysis of the phenomenon of politicization has allowed the identification of three stages: 2000-2004, 2005- 2008, 2009-present. Enforcement of the legislation regarding civil service enabled a considerable increase in stability at this level but there is still a dependence of the public function on the political system through legislative changes.